Perinatal Outcomes With Normal Compared With Elevated Umbilical Artery Systolic-to-Diastolic Ratios in Fetal Growth Restriction. Issue 1 (March 2016) - Maggio, L.; Dahlke, D.; Mendez-Figueroa, H.; Albright, C.M.; Chauhan, S.P.; Wenstrom, K.D.
Abstract : ( Obstet Gynecol. 2015;125:863–869) Growth-restricted and small-for-gestational age (SGA) neonates are at increased risk for perinatal death and severe morbidity, and are also more likely to have health problems in childhood and adult life. Although the American College of Obstetricians and Gynecologists (ACOG) and the Society for Maternal-Fetal Medicine have published guidelines for the use of the umbilical artery systolic-to-diastolic ratio to determine the timing of delivery for these pregnancies, their recommendations are largely based on expert opinions.